2017
DOI: 10.4314/evj.v21i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of ticks infesting cattle reared on the main campus of Haramaya University, Eastern Ethiopia

Abstract: Tick infestation is a major problem constraining animal production and productivity in Ethiopia showing the need for tackling the situation. A crosssectional study was carried out to determine tick prevalence and associated risk factors among cattle reared on dairy, beef and free-range grazing farms of Haramaya University from November 2014 to April 2015. A total of 519 animals were randomly selected. Ticks were collected and identified under stereomicroscopic examination. A total of 384 (73.9%) animals were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(14 reference statements)
1
5
1
Order By: Relevance
“…This finding is in agreement with the previous study of Kassa and Yalew [ 22 ] who reported 33.2% prevalence of ticks in the same study area and Desalegn et al [ 21 ] who reported 25.23% prevalence. However, the finding disagrees with 61–89.4% prevalence reports in different parts of Ethiopia [ 23 , 27 – 31 ]. This difference might be due to the difference in the agroclimatic condition of the study areas and season of sample collection.…”
Section: Resultscontrasting
confidence: 92%
See 3 more Smart Citations
“…This finding is in agreement with the previous study of Kassa and Yalew [ 22 ] who reported 33.2% prevalence of ticks in the same study area and Desalegn et al [ 21 ] who reported 25.23% prevalence. However, the finding disagrees with 61–89.4% prevalence reports in different parts of Ethiopia [ 23 , 27 – 31 ]. This difference might be due to the difference in the agroclimatic condition of the study areas and season of sample collection.…”
Section: Resultscontrasting
confidence: 92%
“…Difference between young and old was statistically significant ( p ≤ 0.05). This finding was strengthened by the finding of Desalegn et al [ 21 ] who reported infestation was higher in more than 3-year-old cattle than in less than 3-year-old cattle and also agrees with finding of different authors [ 18 , 22 , 23 , 31 ] who reported higher proportion in adult cattle. Higher proportion may be due to long-distance movement of adult cattle to search for food which increases the chance of contact to tick and also low immunity in older animals.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The finding of present study, tick's prevalence was highest (70.56%) in the animals allowed for group feeding while lowest (29.44%) in the animals fed individually. Abdella et al (2017) observed significantly lower tick's prevalence in free-range grazing farm (32.4%) than in both beef (79.2%) and dairy farm (82.3%).…”
Section: Season-wise Prevalence Of Tickmentioning
confidence: 76%